2005
DOI: 10.4103/0253-7613.16572
|View full text |Cite
|
Sign up to set email alerts
|

The influence of some azoles on wound healing in albino rats

Abstract: Wound healing, a common clinical entity contemporary to human beings, has been recognized to be influenced by several factors such as nutrients like vit-C, zinc, and hormones like GH, insulin, etc. Products of traditionally used plants such as Bryophyllum pinnatum [1] and Moringa oleifera [2] have also been reported to promote healing in experimental animals, probably by virtue of their antimicrobial activity. Because it is well known that infection interferes with healing, antimicrobials are expected to suppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…In studies with experimental animals, metronidazole solutions at a dosage of 20mg/kg resulted in delayed healing 16 . A similar effect was reported for a dosage of 160mg/kg 13 . Dosages higher than 20 and lower than 160mg/kg promoted an increase of granulation tissue and epithelialization 10 , 12 - 15 .…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…In studies with experimental animals, metronidazole solutions at a dosage of 20mg/kg resulted in delayed healing 16 . A similar effect was reported for a dosage of 160mg/kg 13 . Dosages higher than 20 and lower than 160mg/kg promoted an increase of granulation tissue and epithelialization 10 , 12 - 15 .…”
Section: Discussionsupporting
confidence: 80%
“…The wide variation of metronidazole concentrations for topical use at the experimental level is an additional difficulty. There are studies that report the effects of metronidazole on healing using 20mg/kg 16 , 50mg/kg 14 , 108 mg/kg 10 , 160mg/kg 13 and 180mg/kg 12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated the action of metronidazole administered orally at a dose of 180mg/kg in the tissue repair process, accelerating wound contraction, collagen synthesis and epithelialization and promoting precocity in cicatrization by directly stimulating fibroblasts, the main cells involved in this process. However, higher doses of this drug may produce cytotoxicity in these cells (Rao et al, 2002;Girish and Patil, 2005), by preventing the synthesis of collagen, elastin, fibronectin, glycosaminoglycans and proteases necessary for tissue remodeling during healing (Amadeu et al, 2003;Hildebrand et al, 2005). Also, there are indications that metronidazole does not act directly on the fibroblasts, but rather diminishes the duration of the inflammatory phase, allowing the cells to speed up the healing process (Sampaio et al, 2009), which was reinforced by our study, since there were no sign of inflammatory processes in the implantation sites as well as in the placentas.…”
Section: Discussionmentioning
confidence: 99%